Pengaruh Efektivitas Kredit Dan Fee Base Income Terhadap Kinerja Keuangan Perbankan - Muhamad Ahlan Sopian; Udi Pramiudi (Institut Bisnis dan Informatika Kesatuan, 2021)
The focus of this research is aimed at analyzing the effect of credit effectiveness and fee based income on banking financial performance. Where this financial performance may experience an increase or decrease in the coming year. Due to the uncertain financial performance, it is necessary to have an analysis of the financial performance of a company. The object of this research is the effect of credit and fee base income on the financial performance of PT. Bank Central Asia Tbk. Period 2011-2020. There are two independent variables studied in this study, namely: Credit and fee base income, while Return on assets as the dependent variable. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis, and hypothesis test which includes t test, F test and determination coefficient test ( ). The results of this study indicate that partially credit effectiveness does not have a significant effect on Return on assets with a sig. 0.648> 0.05. Fee income base does not have a significant effect on Return on assets with a sig value. 0.342> 0.05. And simultaneously Credit Effectiveness and Fee Income Base have no significant effect on Return on Assets with a sig value. 0.472> 0.05. Keywords : Credit Effectiveness, Fee Base Income, Return On Asset